Current Perspectives in Mesenchymal Stromal Cell Therapies for Airway Tissue Defects - Francesco Petrella; Stefania Rizzo; Alessandro Borri; Monica Casiraghi; Lorenzo Spaggiari (Stem Cells International)
Lung cancer is the leading cause of cancer death and respiratory diseases are the third cause of death in industrialized countries; for this reason the airways and cardiopulmonary system have been the focus of extensive investigation, in particular of the new emerging branch of regenerative medicine. Mesenchymal stromal cells (MSCs) are a population of undifferentiated multipotent adult cells that naturally reside within the human body, which can differentiate into osteogenic, chondrogenic, and adipogenic lineages when cultured in specific inducing media. MSCs have the ability to migrate and engraft at sites of inflammation and injury in response to cytokines, chemokines, and growth factors at a wound site and they can exert local reparative effects through transdifferentiation and differentiation into specific cell types or via the paracrine secretion of soluble factors with anti-inflammatory and wound-healing activities. Experimental and clinical evidence exists regarding MSCs efficacy in airway defects restoration; although clinical MSCs use, in the daily practice, is not yet completely reached for airway diseases, we can argue that MSCs do not represent any more merely an experimental approach to airway tissue defects restoration but they can be considered as a “salvage” therapeutic tool in very selected patients and diseases.